PENGARUH EKSPOR DAN IMPOR TERHADAP PRODUK DOMESTIK BRUTO INDONESIA TAHUN 2008-2017 - Dea Fitri Febriyanti (Ecoplan, 2019)
This research is conducted to (1) analyze the effect of export and import simultaneous towards Gross Domestic Product of Indonesia in period 2008-2017; (2) analyze the most dominant factors in influencing Gross Domestic Product of Indonesia in period 2008-2017. This research was taken place in Indonesia and using secondary data obtained from the website Badan Pusat Statistik, Kementerian Perdagangan Republik Indonesia and Katadata and than that will made and analyze using multiple linear regression. This analysis will be tested through partial test (the t test) and simultaneous test (the f test). The result of this research shows that in partial export has an effect towards Gross Domestic Product significantly and import has no effect towards Gross Domestic Product significantly. In simultaneous export and import have an effect towards Gross Domestic Product significantly. Exports are the most dominant influence in influencing Gross Domestic Product of Indonesia in period 2008-2017. Keyword : Export, Import, Gross Domestic Product